Society, History and Education: dialogues from a disciplinary perspective (2022)
We are pleased to present to the entire academic community and the general public the following work, which contains recent research results of a group of teachers from the Faculty of Educational Sciences in areas such as pedagogy, communication, technology and history. This publication is the result of the work coordinated by the Vice Rector's Office for Research, Innovation and Extension of the UTP, with the support of the Faculty of Education Sciences, through the realization of the First Conference on Social Appropriation of Knowledge held in 2022, in order to reach a wider field of dissemination of local research. In the first chapter "Sentiment analysis on Twitter about mobile learning" by professors Rosa María Guilleumas García and Hernán Gil Ramírez, a study of tweets about mobile learning is presented. To do so, the authors combined several techniques of social network analysis, text mining and sentiment analysis, using NodeXL software, specialized in network examination and visualization. Among their results, they highlight the great predominance of positive tweets over negative ones in this field of study, and at the same time point out that, in the analyzed tweets, the most used words were learning, mobile, app, machine, mlearning and education. In second place, there is the chapter "The institutional educational project. An opportunity for reflection and transformation of the Colombian university" by teachers Martha Cecilia Gutiérrez Giraldo and Carolina Franco Ossa, which arises from the reflection on university autonomy and its internal exercise in the construction of its Institutional Educational Projects (PEI). Thus, the main purpose of this work is to identify the relevant facts that have marked the academic life of the UTP since its creation in 1958 until 2015, in which the different strata of the university community (teachers, students, administrators, managers, graduates and the social sector) participated through a participatory action research process. The results show that since its creation, the University has updated its academic and management policies in accordance with the regulations in force in each period, and that, at the same time, as mentioned by the authors, the institutional processes of self-reflection and projection of the academic life of the UTP should be strengthened through the culture of academic and democratic participation, supported by the collaborative work of the university community